Rhythmical Learning Program on Musical Notation for Junior High School Online Using the Maestro Application - Azmiyati, Ismi; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Muhammad Roil (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study was to provide an overview to junior high school students regarding rhythmic sounds based on the number of notes through the Maestro application so that students more easily understand and can practice it directly. This research also guides students to be able to read and write rhythmically on musical notes. The focus of the problems studied includes the material being taught, the methods used, and the results obtained. The research method used is a case study through a qualitative approach. The method is used to describe and describe, as well as analyse the phenomenon of rhythmic learning. The learning method used is not only from one method, but there are several other methods such as using environmental media as material for practice and listening to music or songs. The variation of the method aims to make students not feel bored with the material being taught. The object of this research is 10 students from junior high school 22 Bandung, West Java, Indonesia. These results indicate that students' knowledge of music increased from the previous question in the pre-test, which was 7.46%, and after we explained and distributed the post-test questions, the result was 21.37%.